Total Hip Replacement For Ankylosed Hip: A Case Report - Pratama, Rahendra; Afrian, Jifaldi; Chilmi, Mohammad Zaim (Indonesian Hip and Knee Society (IHKS), 2022)
AbstractIntoductionAnkylosis of the hip is very difficult to treat surgically and should only be attempted by an experienced surgeon together with comprehensive pre-operative planning. It is important to inform the patient about the possible complications of this procedure.Case DescriptionMale patient at the age of 68 years with severe left hip pain for the last 30 years. The pain was intermittent,mostly at night, The pain got worse during walk and subside when resting. No history of trauma, TB contact, fever, allergies, alcohol usage or smoking. There was also no history of surgery. X-Ray shows fusion of the left hip. Blood test shows no infection detected.DiscussionPosterior approach was used in this case, inability to internally rotate the hip due to bony fusion will made the osteotomy more difficult. Visualized Greater Trochanter and palpable Lesser trochanter as landmark for osteotomyConclusionTHA is an effective treatment for severe flexion ankylosed/fused hip deformity although there are high surgical complications than routine hip arthroplasties. Adequate preoperative planning will improve the clinical outcome of the hips.